Correlation between radiographic knee osteoarthritis and lifetime cigarette smoking amount in a Korean population: A cross-sectional study. Issue 26 (26th June 2020) - Kim, Jung Woo; Lee, Sang Yoon
Abstract : Abstract: Although the inverse correlation between smoking and degenerative arthritis is controversial, quantitative analysis of the correlation between lifetime cigarette smoking amount and degenerative arthritis has not been performed. We investigated the correlation between knee radiographic osteoarthritis (ROA) and lifetime cigarette smoking amount in the general population. This cross-sectional study used the Fifth and Sixth Korean National Health and Nutrition Examination Survey (2010–2013) data. Subjects included 11, 638 community-dwelling adults aged ≥50 years. Knee ROA was defined as a Kellgren/Lawrence grade ≥2 on plain radiography. Lifetime cigarette smoking amount was calculated in terms of pack-year and further divided into quartile groups. Independent correlation between smoking and knee ROA was determined using odds ratios (OR) adjusted for age, sex, obesity, physical activity, and household income on multivariate logistic regression analysis. Knee ROA prevalence was 37.3%; prevalence of lifetime cigarette smokers was 26.0%. Subjects with knee ROA had higher mean age, female sex ratio, and body mass index but lower physical activity level. The adjusted logistic regression model revealed that female sex (OR, 2.110; 95% confidence interval [CI], 1.895–2.349) was significantly associated with knee ROA. Older age, obesity, and lower household income were positively correlated with knee ROA. Second-and fourth-quartile groups of smokers had the lower ROA prevalence than never-smokers (OR, 0.800; 95% CI, 0.643–0.99; OR, 0.812; 95% CI, 0.684–0.965, respectively). An inverse correlation with knee ROA was confirmed in mid-light to heavy smokers. Prospective studies are needed to reveal whether knee ROA involves smoking.